Pengaruh Free Shipping dan Shopping Lifestyle Terhadap Impulse Buying pada Tiktok Shop - Alpya, Novella; Pramuditha, Charisma Ayu (Universitas Multi Data Palembang, 2025)
This study aims to analyze the effect of free shipping and shopping lifestyle on impulse buying among TikTok Shop platform users. The research employs a quantitative method with a purposive sampling technique, using the Slovin formula to determine the sample size, involving 400 respondents from Generation Z and Millennials in Palembang City. Hypothesis testing was conducted using multiple linear regression analysis with SPSS 26. The results indicate that free shipping has a positive and significant effect on impulse buying, suggesting that waived shipping fees can encourage impulsive purchases. Additionally, shopping lifestyle also has a positive and significant effect on impulse buying, implying that a person's consumption patterns and shopping habits contribute to unplanned purchasing decisions. In conclusion, free shipping and a high shopping lifestyle tendency can increase the likelihood of impulse buying on the TikTok Shop platform.